2025 Japanese Heart Rhythm Society / Japanese Circulation Society Consensus Statement on the Appropriate Use of Ambulatory and Wearable Electrocardiographs - Takanori Ikeda; Takashi Ashihara; Yu‐ki Iwasaki; Maki Ono; Nobuyuki Kagiyama; Takehiro Kimura; Kengo Kusano; Ritsuko Kohno; Keita Saku; Tetsuo Sasano; Keitaro Senoo; Seiji Takatsuki; et al. (Journal of Arrhythmia)
Recently, some clinicians have been diagnosing and treating arrhythmias on the basis of electrocardiogram (ECG) devices with low accuracy. In Europe and the US, several statements on the use of ECGs have already been published by related academic societies. In addition, with the relaxation of regulations on media advertising ambulatory/wearable ECG devices, the frequency of use of simple ECG devices by the general public will increase in the future. Therefore, this statement describes the functions and features of non‐invasive ambulatory or wearable ECG devices that have been approved as medical devices in Japan (and that can record ECGs remotely), as well as points to note when using them; provides an overview of data storage and security for ambulatory/wearable ECG devices and implantable loop recorders (ILRs), as well as discussing differences between their use and the use of non‐invasive ambulatory/wearable ECG devices; and provides classes of recommendation for the use of these devices and their evaluation for each arrhythmia type or condition. We describe lead‐based ambulatory ECG devices (classical 24‐h Holter ECG monitoring), handheld ECG devices, handheld‐based ECG devices using a smartphone, wearable ECG devices (smartwatch and garment ECG devices), and patch ECG devices. In addition, we provide information on methods that are not based on the original ECG, such as photoplethysmography and oscillometric blood pressure measurement, and describe the limitations of their use. We hope that the publication of this statement will lead to the appropriate use of ambulatory/wearable ECG devices in Japan.